Estimation of Global Solar Radiation at Mid Hill Region, Okhaldhunga - Joshi, U.; Karmacharya, A.M.; Shrestha, P.M.; Chapagain, N.P.; Shrestha, P.M.; Karki, I.B.; Poudyal, K.N. (Patan Prospective Journal, 2022)
Global solar radiation knowledge can be valuable in fulfilling energy demands and exploring numerous applications of solar technology. Since only a few meteorological stations are available and the installation of additional stations is complicated because the cost is very high, a comparative study of various models is essential for accurate global solar radiation prediction rather than measurement. In the present study, four models based on sunshine hour, temperature, and relative humidity for estimating daily global solar radiation were compared using the regression technique for Okhaldhunga (Lat.27.30810 N, Lon.86.50420 E, Alt.1720m.a.s.l.). These models were evaluated and compared based on four statistical error tests. The basis of analysis, model M4, which uses sunshine hour, maximum temperature, and relative humidity, was used for estimating daily global solar radiation with acceptable accuracy. The empirical constants obtained for M4 models were a=0.62, b=0.47, c= -0.003, and d= -0.003. The site's annual average global solar radiation was 4.16 kWh/m2 /day. The results of this study help estimate global solar radiation for similar geographical locations in Nepal.